Beyond bridging the know-do gap: a qualitative study of systemic interaction to foster knowledge exchange in the public health sector in The Netherlands - van den Driessen Mareeuw, Francine (BMC Public Health, 2015)
BACKGROUND: Despite considerable attention currently being given to facilitating the use of research results in public health practice, several concerns remain, resulting in the so-called know-do gap. This article aims to identify the key tensions causing the know-do gap from a broad perspective by using a systemic approach and considering the public health sector as an innovation system. METHODS: An exploratory qualitative design including in-depth semi-structured interviews was used, with 33 interviewees from different actor categories in the Dutch public health innovation system. The analyses employed an innovation system matrix to highlight the principal tensions causing the know-do gap. RESULTS: Seven key tensions were identified, including: research priorities determined by powerful players; no consensus about criteria for knowledge quality; different perceptions about the knowledge broker role; competition engendering fragmentation; thematic funding engendering fragmentation; predominance of passive knowledge sharing; and lack of capacity among users to use and influence research. CONCLUSIONS: The identified tensions indicate that bridging the know-do gap requires much more than linking research to practice or translating knowledge. An innovation system perspective is crucial in providing information on the total picture of knowledge exchange within the Dutch public health sector. Such a system includes broader stakeholder involvement as well as the creation of social, economic, and contextual conditions (achieving shared visions, building networks, institutional change, removing financial and infrastructural barriers), as these create conducive factors at several system levels and induce knowledge co-creation and innovation.